Ambidextrous Leadership and Employee Voice Behavior: The Role of Work Motivation and Ambidextrous Culture - Ouyang C; Zhu Y; Ma Z (Psychology Research and Behavior Management, 2022)
Chenhui Ouyang, Yongyue Zhu, Zhiqiang Ma School of Management, Jiangsu University, Zhenjiang, People’s Republic of ChinaCorrespondence: Yongyue Zhu, School of Management, Jiangsu University, Zhenjiang, People’s Republic of China, Tel +86 13914553150, Email zhuyy@ujs.edu.cnPurpose: In the current competitive environment of increased uncertainty and instability, it is of significance to promote employee voice behavior. To discuss the issue of how to promote employee voice behavior both effectively and reasonably, this study focuses on ambidextrous leadership, which consists of two seemingly opposite yet potentially complementary behaviors—transformational and transactional leadership—and investigates its influence mechanism on employees’ voice behavior, using work motivation as a mediator and ambidextrous culture as a moderator.Methods: Enterprise employees and their direct supervisors from 78 work teams in China were surveyed, and 387 sets of paired data were analyzed using data analysis software, such as HLM, SPSS, and AMOS.Results: The results reveal that ambidextrous leadership can significantly positively predict employee voice behavior. Employee work motivation plays a partial mediating role in the positive correlation between ambidextrous leadership and voice behavior. Additionally, organizational ambidextrous culture positively moderates the correlation between ambidextrous leadership and the work motivation of employees. The greater the ambidextrous culture of teams is, the stronger the positive correlation between ambidextrous leadership and the work motivation of employees.Conclusion: Leadership plays an important role in promoting employee voice behavior. Therefore, understanding how ambidextrous leadership style can effectively promote voice behavior is important for companies to utilize the power of their employees to respond quickly to change and drive innovative transformation. This study contributes to existing research by revealing how ambidextrous leadership impact employee voice behavior through work motivation, which provides new evidence for the emerging ambidextrous leadership theory and helps to understand the relationship between employee work motivation and voice behavior more comprehensively; it also identifies organizational ambidextrous culture as organizational context factor which moderate the effect of ambidextrous leadership on work motivation.Keywords: ambidextrous leadership, employee voice behavior, work motivation, organizational ambidextrous culture